Strengthening Understanding of Constitutional Law Through Contextual Learning Based on Current Issues in Malang City - Rika Novitasari; Tikka Dessy Harsanti (Jurnal Ilmu Politik dan Studi Sosial Terapan, 2025)
This study aims to analyze the effectiveness of contextual learning based on current legal and political issues in strengthening law students’ understanding of Constitutional Law at law faculties in Malang City. This research employed a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation involving lecturers and students enrolled in Constitutional Law courses. The findings reveal that contextual learning enhances students’ ability to comprehend fundamental constitutional concepts and connect them with real-life legal and political phenomena such as elections, legislative amendments, and government policies. Students became more active and critical in formulating constitutional arguments, while lecturers acted as facilitators guiding discussions around contemporary legal issues. In addition to improving conceptual understanding and constitutional awareness, the study identifies several challenges, including limited instructional time and students’ varying levels of digital literacy in evaluating the credibility of online legal sources. These findings confirm that contextual learning based on current issues is an effective pedagogical strategy to bridge the gap between legal theory and practice, fostering reflective competence among law students in the digital transformation era.